Mapping lymphocyte plasma membrane proteins: a proteomic approach. - Peirce, M; Saklatvala, J; Cope, A; Wait, R (2007)
The pathological importance of tumor necrosis factor (TNF)-alpha in rheumatoid arthritis (RA) is now widely accepted. Ex vivo data from synovial cell cultures suggest that direct cell contact between activated T-cells and macrophages may be an important driver of macrophage TNF-alpha production in the RA joint. However, the ligand/receptor pairs driving this cell contact signal remain obscure. One reason for this is that plasma membrane (PM) proteins are resistant to systematic analysis using traditional proteomic approaches. In this chapter we present a method for the enrichment and resolution of PM proteins from murine T-cell hybridomas as a prelude to identification by tandem mass spectrometry. We used cell surface biotinylation, differential centrifugation and subsequent streptavidin affinity capture, followed by solution phase iso-electric focussing and tandem mass spectrometry to identify 75 PM proteins and make semiquantitative comparisons of resting and activated cells. The method is applicable to a wide variety of cell types.